PENGARUH INDEPENDENSI, PENGALAMAN, PENDIDIKAN, ETIKA DAN GENDER TERHADAP PROFESIONALISME AUDITOR - Rezca Setiawan; Kamaliah '; Al Azhar L ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
Professionalism is one of the main things that must be owned by an auditor in performing his duties and is the main requirement for the profession. In the process of implementation of the state financial audit of the management, professionalism of auditors is influenced by many factors. This study aims to look at the effect of the independence, experience, education, ethics and gender in the professionalism of Auditor The Audit Board of the Republic of Indonesia Representatives of the Province of Riau and West Sumatra Province. The population in this study are all auditors who actively work in the Audit Board of the Republic of Indonesia Representatives of the Province of Riau and West Sumatra Province with a total of 190 auditors, each representative only deign given a questionnaire of 50 questionnaires so that researchers had 100 respondents and choose whole being sampled in this study, sampling is done by a random method. Methods of data analysis using multiple linear regression with SPSS 17.00. The results showed that the independence of auditors, auditor experience, ethics, and gender affect the professionalism of auditors. While education has no effect on the professionalism of auditors.Keywords : Independence, Experience, Education, Ethics, Gender and Auditor Professionalism